The Utilization of Instagram as a Media Promotion : the Case Study of Library in Indonesia - Muhammad Azwar; Siti Sulthonah (Insaniyat : Journal of Islam and Humanities, 2018)
This paper aims to explore the Instagram utilization and its obstacles as a media promotion of Pustakalana’s library in Bandung, West Java. The research uses qualitative approach. The informants of this research are Pustakalana’s Instagram administrator and Pustakalana’s coordinator, while data collection techniques consist of observation, interview, literature study, and documentation. Triangulation method is used to test data validity and credibility. Technical data analysis involves of data reduction, data presentation, and conclusion. The results of this study indicate that Pustakalana’s library has been utilized the Instagram to promote its library, such as various activities and services growing children’s creativity and imagination, events and workshops for parents, photographs of popular and recommended book collection, quotes to motivate children to read, and the atmospheres of the library and bookstore which are convenient and exciting, and another library services information. Instagram of Pustakalana’s library is not only used for promoting its activities, but also for sharing information and communication by its followers in media. Instagram features are almost entirely utilized by the library on promotions and interactions in other social media. The promoted content in Instagram account contains all information that relate to the library. Nevertheless, they are obstacles emerge in Pustakalana’s Library such as the incompatibility between the number of followers with the number of likers who are obtained on each uploaded post, and the lack of human resources. DOI: 10.15408/insaniyat.v2i2.7320